Beginning MapServer: Open Source GIS Development - Kropla, Bill (Apress, 2012)
Maps have played a prominent role in human activity for thousands of years. One of the earliest known maps was uncovered during the course of an archaeological excavation in Turkey in 1961. The Çatalhöyük site is a neolithic settlement dating from approximately 6500 BC. The map consists of a partially preserved, painted plaster representation of the community in plan view, with a smoking volcano in the background. While not drawn to scale, the map does seem to preserve the relative orientation of the structures represented. Figure 1 is a modern rendering of a portion of the original wall fragment.